Peripapillary and parafoveal vascular network assessment by optical coherence tomography angiography in aquaporin-4 antibody-positive neuromyelitis optica spectrum disorders. Issue 6 (18th July 2018) - Huang, Yongheng; Zhou, Lei; ZhangBao, Jingzi; Cai, Tongjia; Wang, Bei; Li, Xiaoyang; Wang, Liang; Lu, Chuanzhen; Zhao, Chongbo; Lu, Jiahong; Quan, Chao; Wang, Min
Abstract : Background/aims: Current understanding of the alterations in the retinal vascular network in neuromyelitis optica spectrum disorders (NMOSDs) is limited. We aim to assess the peripapillary and parafoveal vessel density in aquaporin-4 antibody-positive NMOSD patients by optical coherence tomography (OCT) angiography. Methods: A total of 55 aquaporin-4 antibody-positive NMOSD patients with or without a history of optic neuritis (ON) and 33 healthy controls underwent spectral domain OCT and OCT angiography. Clinical histories, Expanded Disability Status Scale score, visual functional system score (VFSS) and disease duration were collected. Results: Peripapillary and parafoveal vessel density was significantly decreased in NMOSD eyes with or without a history of ON. The decrease in retinal vessel density could occur before ON and retinal nerve fibre layer (RNFL) atrophy. Peripapillary vessel density correlated well with the spectral domain OCT measurements and VFSS in NMOSD eyes with a history of ON. Conclusion: Subclinical primary retinal vasculopathy may occur in NMOSD prior to ON and RNFL atrophy. Peripapillary vessel density might be a sensitive predictor of visual outcomes in NMOSD patients with ON.